Effect of thermal Barrier coating in CI engines fueled with Citrus Medica (Citron) peel oil biodiesel dosed with cerium oxide nanoparticle. (2021) - Shanmugam, Mohanraj; Sathiyamurthy, S.; Rajkumar, G.; Saravanakumar, S.; Tamil Prabakaran, S.; Shaisundaram, V.S.
Abstract: In modern days, due to the increase in the automobile pollution and energy crisis has been major concern that world is facing. So, discovering a alternate source of fuel that can partially replace the conventional fuel sources is certainly necessary. Biodiesel is one such alternate fuel source that can fractionally meet the energy requirement. Additionally, control of Green House Gases (GHG) also plays a vital role in conserving the environment. In the present research article, the emission and performance characteristics of Citrus Medica Peel Oil bio diesel dosed with Cerium Oxide (CeO2 ) nano particle additive was studied. As well the engine cylinder liner and piston head were coated with Thermal Barrier Coating (TBC) of thickness 300 µm and 150 µm respectively to furthermore improve the performance characteristics. TBC was done with Zirconia Stabilized with Yttria and Ceria (Zirconia 85%, Yttria 10%, and Ceria 5%). Air Plasma Spray Technique (APS) was employed to carry out the coating. Finally, the emission and performance analysis were carrier out with DCO, B15, B20, B25 blends in single cylinder compression ignition engine with TBC and with and without TBC under same testing conditions. It was found that Brake Thermal Efficiency (BTE) of B20 + 15 ppm was marginally higher and with TBC the Specific Fuel Consumption is reduced by 10.59% and there was rise in frictional power loss. The Exhaust Gas Temperature (EGT) escalated by 8-15⁰C. Regarding the emissions, there was accountable decline in Carbon monoxide (CO), Carbon dioxide (CO2 ) and oxides of Nitrogen (NOx). The morphology of coating remained undifferentiated after 20 h of uninterrupted operation of engine but with only excess carbon deposits on the surface.